(untitled) (Scientific journal of the Fergana State University, 2026)
The article presents an analysis of herbarium specimens collected by scientists conducting research in the Katta and Kichik O’radarya basins, stored in the National Herbarium of Uzbekistan (TASH) and collected during field research. The use of herbariums and their importance in preserving plant biodiversity are also briefly described. As a result of the study, the first list of medicinal plants of the flora of the region was compiled, including 603 herbarium specimens of 50 species belonging to 26 families and 47 genera. Of these, 8 specimens of 2 species belonging to 2 families and 2 genera were included in the list compiled on the basis of the “Red Book of the Republic of Uzbekistan” (2019). This research work is being carried out within the framework of the project "Taxonomic revision of polymorphic plant families of the flora of Uzbekistan" (FZ-20200929321) of the Institute of Botany of the Academy of Sciences and the state program "Network systematic mapping of the flora of the South-Western Hissar district (part of the Kashkadarya region)", as well as the researcher’s dissertation work.